2020
DOI: 10.1111/bph.15327
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of NaV1.7 channels as an analgesic target: Why has excellent in vitro pharmacology not translated into in vivo analgesic efficacy?

Abstract: In 2006, humans with a congenital insensitivity to pain (CIP) were found to lack functional Na V 1.7 channels. In the subsequent 15 years there was a rush to develop selective inhibitors of Na V 1.7 channels with the goal of producing broadly effective analgesics without the problems of addiction and tolerance associated with opioids.Pharmacologically, this mission has been highly successful, leading to a number of highly potent and selective inhibitors of Na V 1.7 channels. However, there are very few example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 151 publications
(252 reference statements)
1
40
0
Order By: Relevance
“…Consistently, Pn3a treatment was ineffective in rodent models of acute nociception or inflammatory pain, also in agreement with studies where other Na v 1.7 modulators were assayed such as the VSD-peptide ProTx-II ( Schmalhofer et al, 2008 ) and small molecule PF-04856264 ( Deuis et al, 2017 ). The overall contribution of Na v 1.7 to pain in some animal behaviour-based models has been questioned ( Shields et al, 2018 ), whereas research and development of multiple potent and selective Na v 1.7 inhibitors have failed to recapitulate the pain-free state that characterized CIP in humans ( Eagles et al, 2020 ). Importantly, the genetic ablation of SCN9 A in mice and in a human CIP patient, the absence of functional Na v 1.7 leads to increases in endogenous opioid-dependent analgesia and diminished pain-induced peripheral nociceptive drive ( Minett et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, Pn3a treatment was ineffective in rodent models of acute nociception or inflammatory pain, also in agreement with studies where other Na v 1.7 modulators were assayed such as the VSD-peptide ProTx-II ( Schmalhofer et al, 2008 ) and small molecule PF-04856264 ( Deuis et al, 2017 ). The overall contribution of Na v 1.7 to pain in some animal behaviour-based models has been questioned ( Shields et al, 2018 ), whereas research and development of multiple potent and selective Na v 1.7 inhibitors have failed to recapitulate the pain-free state that characterized CIP in humans ( Eagles et al, 2020 ). Importantly, the genetic ablation of SCN9 A in mice and in a human CIP patient, the absence of functional Na v 1.7 leads to increases in endogenous opioid-dependent analgesia and diminished pain-induced peripheral nociceptive drive ( Minett et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations lead to increased interest in discovery of a highly selective and potent inhibitors of Na v 1.7 to reduce the side effects seen in pan Na v channel inhibitors. However, Na v 1.7 inhibitors have for the most part failed to reproduce the pain-free state observed in chronic insensitivity to pain (CIP) ( Eagles et al, 2020 ). Subsequently it was shown that genetic deletion of SCN9A in both mice and humans, that the absence of functional Na v 1.7 but not Na v 1.8, increases endogenous opioid receptor (OR) analgesia via upregulation of the enkephalin precursor Penk mRNA, which could be inhibited by the OR antagonist, naloxone ( Minett et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a concerted effort by pharmaceutical companies to develop selective Na v 1.7 channel inhibitors, the clinical efficacy has been disappointing (28). However, it is not clear that the target has been tested comprehensively in the clinic, as no assays of target modulation were used.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the years that have elapsed since then, it has been increasingly clear that translation from in vitro studies and preclinical studies conducted with rodent models to humans is extremely challenging. Many of the excellent pharmacology studies conducted with in vitro and preclinical models do not translate into in vivo analgesic efficacy [93]. Furthermore, many of the drug pipelines do not test promising candidates in an appropriate translational large animal model and jump straight from mice to men [94].…”
Section: Ion Channels and Painmentioning
confidence: 99%